2009
DOI: 10.1021/nn900779f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orientation on Plasmonic Coupling between Gold Nanorods

Abstract: Radiative coupling of induced plasmonic fields in metal nanoparticles has drawn increasing attention in the recent literature due to a combination of improved experimental methods to study such phenomena and numerous potential applications, such as plasmonic nanoparticle rulers and plasmonic circuitry. Many groups, including ours, have used a near-exponential fit to express the size scaling of plasmonic coupling. First, we show experimental agreement between previously simulated nanorod coupling and plasmonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
201
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(217 citation statements)
references
References 44 publications
14
201
2
Order By: Relevance
“…This interesting scaling behavior, which was found to be valid for various particle shape and size [36][37][38][39][40], provides us a simple and convenient method for the study and application of the plasmon coupling effect. Nonetheless, the accuracy of Plasmon…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…This interesting scaling behavior, which was found to be valid for various particle shape and size [36][37][38][39][40], provides us a simple and convenient method for the study and application of the plasmon coupling effect. Nonetheless, the accuracy of Plasmon…”
Section: Introductionmentioning
confidence: 55%
“…It has been suggested that, instead of the cubic size decay predicted by the simple point-dipole model, the size scaling of this plasmon coupling can be well described with a universal exponential distance dependence (or Plasmon Ruler Equation) [29,[36][37][38][39][40] …”
Section: Introductionmentioning
confidence: 99%
“…Full numerical studies based on the solution of the classical Maxwell's equations have been performed [24,50,[58][59][60][61][62], as well as semi-analytical studies based on transformation optics are available [43,44,63]. The system has also been investigated using non-local hydrodynamic descriptions [35,[43][44][45][46], and recently the full quantum studies using time dependent density functional theory (TDDFT) have been reported [35][36][37].…”
Section: Model and Computational Aspectsmentioning
confidence: 99%
“…Characterization and well-defined excitation of such eigenmodes is important in order to achieve welldefined functionality in devices [2,3] and to successfully apply techniques of coherent control [4][5][6][7]. Nanoantennas consisting of two strongly coupled particles can serve as a model system to study the impact of mode selectivity [6,8,9]. Upon illumination nanoantennas confine and enhance optical fields [10,11] and can therefore be used to tailor the interaction of light with nanomatter [12].…”
Section: Introductionmentioning
confidence: 99%